Literature Review: The Contribution of The Concepts of Tarbiyah, Ta‘Līm, and Ta‘Dīb to the Character Formation of Students in the Contemporary Era - Raehang; Nurdin (Dirasah: Jurnal Pendidikan Islam, 2025)
This study is a systematic literature review that aims to analyze the contribution of the concepts of tarbiyah, ta‘līm, and ta‘dīb to character formation in students during the contemporary era. The focus lies on how these three concepts can be integrated as the main pillars of Islamic education, encompassing intellectual, spiritual, and moral dimensions holistically. Data were obtained through the selection of scholarly articles indexed in Google Scholar and Scopus from 2014–2024, analyzed using a thematic approach based on the PRISMA protocol. The findings indicate that tarbiyah functions as holistic personality development, ta‘līm serves as the transmission of value-laden knowledge, and ta‘dīb plays a crucial role in instilling adab and ethics. When implemented integratively, these three elements can address the challenges of Islamic education in the digital era and strengthen the development of students' religious, ethical, and adaptive character. This study emphasizes the need for an Islamic education framework that focuses not only on knowledge acquisition but also on shaping the complete human being (insān kāmil) through the harmony of intellect, heart, and action.